T-bet deficiency reduces atherosclerosis and alters plaque antigen-specific immune responses - Buono, Chiara (National Academy of Sciences, 2005)
The influence of the immune system on atherosclerosis involves both helper T (Th) cell and antibody responses to plaque antigens. These responses may have proatherogenic and protective effects. T-bet is a transcription factor required for Th1 differentiation and regulates the balance between Th1 and Th2 responses in inflammatory diseases. To clarify how helper T cell subset differentiation influences atherosclerosis, we compared lesion development and immune responses to plaque antigens in low-density lipoprotein receptor-deficient (Ldlr(-/-)) mice with or without functional T-bet genes. Atherosclerosis was significantly reduced in T-bet-deficient Ldlr(-/-) mice compared with Ldlr(-/-) controls, and the lesions that did develop in the absence of T-bet had less smooth muscle cell content. Furthermore, T-bet deficiency caused a Th2 switch in the response to the atherosclerosis-associated antigen heat shock protein-60, and a change in T-dependent isotypes of oxidized LDL-specific antibodies. Of particular significance, T-bet deficiency caused a >250% increase in the titer of E06 antibodies, which are known to be atheroprotective and whose production by B-1 B cells is enhanced by IL-5. These findings establish that T cell subset differentiation influences both T cell and antibody responses that modulate atherosclerosis, and validate the therapeutic goal of skewing T responses to atherosclerosis-associated antigens.